2022
DOI: 10.1097/inf.0000000000003460
|View full text |Cite
|
Sign up to set email alerts
|

Very Low Incidence of SARS-CoV-2, Influenza and RSV but High Incidence of Rhino-, Adeno- and Endemic Coronaviruses in Children With Acute Respiratory Infection in Primary Care Pediatric Practices During the Second and Third Wave of the SARS-CoV-2 Pandemic

Abstract: Respiratory viruses were detected by multiplex-polymerase chain reaction from oropharyngeal swabs in 114/168 (67.9%) children with acute respiratory infection presenting to 5 pediatric practices in Germany between November 2020 and April 2021. In contrast to rhino- (48.8%), adeno- (14.3%) and endemic coronaviruses (14.9%), SARS-CoV-2 and influenza virus were detected only once; respiratory syncytial virus was not detected. This demonstrates differing impacts of pandemic infection control measures on the spread… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 18 publications
(31 reference statements)
2
21
0
1
Order By: Relevance
“…This percentage was significantly lower when compared to the one found in the same time period in 2018–2019 (54.1%); p < 0.001. This is in the range of the results from other studies, which have reported from 15% to 68% of viral detections within their samples [ 8 , 9 , 26 ]. The difference between periods can easily be explained by the fact that, during the pandemic, oropharyngeal or nasopharyngeal samples were collected from most children attending the hospital, while during the pre-pandemic period only children with acute respiratory infection were tested.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This percentage was significantly lower when compared to the one found in the same time period in 2018–2019 (54.1%); p < 0.001. This is in the range of the results from other studies, which have reported from 15% to 68% of viral detections within their samples [ 8 , 9 , 26 ]. The difference between periods can easily be explained by the fact that, during the pandemic, oropharyngeal or nasopharyngeal samples were collected from most children attending the hospital, while during the pre-pandemic period only children with acute respiratory infection were tested.…”
Section: Discussionsupporting
confidence: 75%
“…These preventive measures useful in containing COVID-19 transmission were not specific to SARS-CoV-2 and seemed to affect the circulation of other respiratory viruses. Many countries have reported changes in viral seasonality during the pandemic, with the disappearance, among others, of enveloped viruses, such as influenza or respiratory syncytial virus (RSV) [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Non-enveloped viruses, including rhinovirus or adenovirus, kept circulating during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…In a multicentre prospective study of primary care paediatric practices in Germany between November 2020 and April 2021, rhinovirus was the most commonly detected respiratory virus among children with ARI, while SARS-CoV-2 and influenza virus infections were minimally detected 108 . Among children in Thailand seeking care, there was a notable increase in cases of ILI caused by rhinovirus in July 2020, which were replaced by RSV-associated ILI cases later in the season 109 .…”
Section: Respiratory Disease Associated With Non-sars-cov-2 Virusesmentioning
confidence: 99%
“…Reductions in incidence, as well as shifts in timing, have been reported worldwide during the pandemic for other respiratory viruses such as influenza and RSV[4044]. Resurgences following the subsequent lifting of social distancing measures have also been documented, driven by age-dependent patterns of immunity to different pathogens in a population[4548]. Here, we identified the co-circulation of multiple respiratory pathogens in this cohort, including SARS-CoV-2, Influenza A, and RSV.…”
Section: Discussionmentioning
confidence: 99%